Pheri Culture based Ecological Adaptation Practices of Phree Community in Nepal in the Face of Climate Change - Jogi, Krishna (NPRC Journal of Multidisciplinary Research, 2026)
Background: In environmentally fragile hill regions, Indigenous peoples face accelerating climate variability, yet their locally based responses to climate remain largely understudied. The Phree, a historically marginalized Indigenous group in eastern Nepal, maintains a distinct Pheri tradition that structures their social organization, cosmology, and relationships with the natural world. This study examines culturally informed knowledge, and practices that frame local responses to environmental change.Methods: The study adopted a qualitative ethnographic design grounded in cultural ecology and Indigenous Knowledge Systems. Fieldwork was conducted from May to October 2025 in two Phree-dominated villages in Tehrathum district. Participant observation, semi-structured interviews, focus group discussions, and life histories with elders, ritual specialists, farmers, women, and youth contributed to data generation and enabled intergenerational and gender-sensitive analysis.Results: Ritual institutions, belief systems, and social practices emerged as adaptive mechanisms. Rituals centered on ancestral deities, land, forests, stones, and weather reinforce conservation ethics, regulate agricultural timing in harmony with the seasons, and sustain collective responsibility throughout society. Complementary material strategies include reciprocal labour systems, drought-sensitive cropping adjustments, localized irrigation innovations, and livelihood diversification. The symbolic and material dimensions of adaptation interrelate synergistically to strengthen resilience amid climatic stress.Conclusion: The Phree people are active agents of environmental adaptation, integrating spiritual cosmologies with practical livelihood strategies. Adaptation is embedded in social relations, ritual obligations, and place-based knowledge, rather than being solely technical or reactive.Novelty: This study provides the first in-depth ethnographic account of Phree adaptive strategies and advances a dual cognized-operational framework that reframes ritual life as a form of environmental governance.